Reliability properties and their indicators - Steblyuk, V. (Запоріжжя : 2024, 2024)
EN: Changes in the performance properties of cars and their elements, given to them during design and manufacture, are due to their interaction with factors characterizing operating conditions: load, speed, climatic, etc. The action of these factors has a significant influence on vehicle reliability. Reliability is understood as the property of a product, unit or mechanism to perform specified functions, maintaining established performance indicators over time within specified limits corresponding to specified modes and conditions of use, maintenance, repairs, storage and transportation. The frequency of failures reflects the failure-free property of an object. Elimination of failures is associated with the exclusion of the vehicle from operation for a certain period of time (downtime), labor and material costs. Downtime and costs depend on the maintainability properties of the technical system. The operating time of a part before failure occurs is called its resource and characterizes its durability. For such a complex object as a car, the failure of an element (part, assembly unit, unit) does not, as a rule, determine the durability of the car as a whole. However, an increase in the number of failures leads to the need to remove this vehicle from service, which determines the durability of the vehicle as a whole.
Keywords: vehicle reliability; elimination of failures; maintainability; storability